Agile and business analysis : practical guidance for IT professionals - Girvan, Lynda; Paul, Debra (BCS Learning & Development, 2017)
Adopting an Agile approach can revolutionize the way business analysts work. This book provides a comprehensive introduction to Agile methodologies and how these can be applied to business analysis.